Which beta is best? On the information content of option-implied betas - Rainer Baule; Olaf Korn; Sven Saßning (University of Cologne, Centre for Financial Research (CFR), 2013)
Option-implied betas are a promising alternative to historical beta estimators, because they are inherently forward-looking and can incorporate new information immediately and fully. Recently, different implied beta estimators have been developed in previous literature, but very little is known about their properties and information content. This paper presents a first systematic comparison between six different implied beta estimators, which provides some guidance for applications and identifies directions for further improvements. The main results of the empirical study reveal that betas derived from implied variances are better predictors of realized betas than betas obtained from implied skewness, and that cross-sectional information from all stocks in the market improves beta estimation significantly. We also find that option-implied betas generally have a higher information content in periods of relatively high trading activity in options markets.
Keywords: G11; G12; G13; G14; G17; 330; beta; option-implied information